FACTORS THAT INFLUENCE IN SEDENTARY LIFESTYLE OF STUDENTS OF FOURTH CYCLE OF A PUBLIC HIGH SCHOOL - Álvarez Bogantes, Carlos (2015)
There is sufficient evidence to say that women as they move into the education system to reduce physical activity levels of sedentary lifestyle that put them at higher risk for non-communicable diseases. This led to determine the reasons for the inactivity of a group of fourth cycle. In order to address this problem, a qualitative design using focus groups and depth interviews was used, applied to30 women of high school participated. The results indicate that the participants are unaware of the benefits that can give them an active life, possibly affecting their movement behavior. A key element that have expressed is little impact of physical education classes when promoting lifestyles movement of the participants in this study, especially for ignoring the needs and barriers that students have. Become clear that the sport orientation of physical education classes and lack the skills to participate in activities successfully, sedentary activities of friends, the attitudes of parents; curriculum and lack of facilities also have significant impact in the studied group.